2020
DOI: 10.3390/life10090165
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular System in COVID-19: Simply a Viewer or a Leading Actor?

Abstract: As of January 2020, a new pandemic has spread from Wuhan and caused thousands of deaths worldwide. Several studies have observed a relationship between coronavirus disease (COVID-19) infection and the cardiovascular system with the appearance of myocardial damage, myocarditis, pericarditis, heart failure and various arrhythmic manifestations, as well as an increase in thromboembolic risk. Cardiovascular manifestations have been highlighted especially in older and more fragile patients and in those with multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
0
15
0
1
Order By: Relevance
“…73 In a study of 4,526 patients with Covid-19 across the world, almost 18% had arrhythmia. 73 Atrial arrhythmia was the most frequent (81.8%), followed by bradyarrhythmia (22.6%), and ventricular arrhythmias (20.7%). 74 Potassium plays a crucial role in modifying resting membrane potential, thus deviations from normal potassium levels results in electrophysiological perturbations and unfavorable effects on the cardiac electrophysiology.…”
Section: Potassium Abnormalities and Cardiac Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 In a study of 4,526 patients with Covid-19 across the world, almost 18% had arrhythmia. 73 Atrial arrhythmia was the most frequent (81.8%), followed by bradyarrhythmia (22.6%), and ventricular arrhythmias (20.7%). 74 Potassium plays a crucial role in modifying resting membrane potential, thus deviations from normal potassium levels results in electrophysiological perturbations and unfavorable effects on the cardiac electrophysiology.…”
Section: Potassium Abnormalities and Cardiac Dysfunctionmentioning
confidence: 99%
“…Elevated troponin enzymes and creatine kinase‐myocardial band (CK‐MB), as diagnostic markers of myocardial injury, have been reported in many SARS‐CoV‐2 cases 72 . Direct viral invasion through the ACE2 receptors, advanced release of inflammatory cytokines, and a mismatch between myocardial oxygen supply and demand are the possible mechanisms of myocardial damage and subsequent arrhythmia 73 . In a study of 4,526 patients with Covid‐19 across the world, almost 18% had arrhythmia 73 .…”
Section: Potassium Abnormalities and Cardiac Dysfunctionmentioning
confidence: 99%
“…In fact, they had a lower Charlson comorbidity index than hospitalized patients and fewer underlying chronic diseases. The association between the presence of chronic diseases and severe forms of COVID-19 are known [ 1 , 2 , 16 , 17 , 18 ]. For example, Zhou [ 1 ] et al showed that comorbidities were present in nearly half of hospitalized patients, with hypertension being the most common, followed by diabetes and coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infects the host using the ACE-2, a membrane-bound peptidase, expressed more in the kidney than in other organs (lung, heart, intestine, and endothelial cells). [24][25][26] While ACE converts angiotensin I (Ang I) to angiotensin II (Ang II), ACE2 degrades Ang II to angiotensin 1-7 [Ang- (1)(2)(3)(4)(5)(6)(7)]. Ang II plays a role in vasoconstriction and adrenergic stimulation, binding type 1 Ang II receptors (AT1), 27 while Ang-(1-7) opposes the Ang II-AT1 axis through vasodilatation, and antiinflammatory and anti-fibrotic action, mainly increasing the production of nitric oxide.…”
Section: Pathogenesis Of Kidney Injurymentioning
confidence: 99%
“…3,4 The ability of the virus to bind the ubiquitous angiotensin-converting enzyme (ACE)-2 receptors allows SARS-CoV-2 to target organs other than the lungs, such as the heart, central nervous system, gastrointestinal tract, etc. 5,6 At present, the kidney is one of the several targets of COVID-19, but, as initially misdiagnosed, its involvement was considered negligible. However, acute kidney injury (AKI) in patients with COVID-19 is considered a marker of disease severity and a negative prognostic factor for survival.…”
Section: Introductionmentioning
confidence: 99%